Chronobiological Analysis of Blood Pressure in a Patient with Atrial Fibrillation at the Development of Heart Failure and Its Therapeutic and Surgical Treatment - Sergey Chibisov; George Katinas; Inna Brodskaya; Aleksandr Ertman; Grigory Gromyko; Aleksandra Konradi; Oleg Mamontov; Anna Merkuryeva; Ekaterina Polunicheva; Evgeny Shlyakhto; Anna Soboleva; Sergey Yashin; et al. (Cardiology Research and Practice)
Dynamics of blood pressure (BP) and heart rate (HR) was traced by automatic monitoring every 30 min uninterruptedly along several months in a patient suffering from combined atrial fibrillation and heart failure during the development of disease and its therapeutic and surgical treatment (pacemaker implanting and atrioventricular ablation). Analyses of spectral components as well as signal’s shape revealed instabilities in circadian and semicircadian parameters. A new approach for signal’s form description without using cosine approximation is suggested. The meaning that referring a patient as dipper, night peaker, or nondipper might be useful at choosing tactics of his treatment is impugned, because all these “types” can transform themselves in the same person in few days. Optimization timing of treatment provides better results if not the “types” of daily profile would be taken to account but the real form of the BP-signal and timing its first and second derivatives.